2004
DOI: 10.4049/jimmunol.172.3.1463
|View full text |Cite
|
Sign up to set email alerts
|

Production of Donor T Cells Is Critical for Induction of Donor-Specific Tolerance and Maintenance of Chimerism

Abstract: Nonmyeloablative conditioning has significantly reduced the morbidity associated with bone marrow transplantation. The donor hemopoietic cell lineage(s) responsible for the induction and maintenance of tolerance in nonmyeloablatively conditioned recipients is not defined. In the present studies we evaluated which hemopoietic stem cell-derived components are critical to the induction of tolerance in a total body irradiation-based model. Recipient B10 mice were pretreated with mAbs and transplanted with allogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 40 publications
(41 reference statements)
3
69
1
Order By: Relevance
“…This result also suggested that DNTreg could be used in a broad range for treatment. Previous studies have demonstrated that early mixed chimerism may not always persist over the long term, particularly with regimens that involve a combination of immunosuppressive techniques [34,35]. Hence, tolerance in mixed chimerism must be more carefully assessed in the setting of transplantation, owing to the possibility that chimerism may be dissociated with tolerance [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…This result also suggested that DNTreg could be used in a broad range for treatment. Previous studies have demonstrated that early mixed chimerism may not always persist over the long term, particularly with regimens that involve a combination of immunosuppressive techniques [34,35]. Hence, tolerance in mixed chimerism must be more carefully assessed in the setting of transplantation, owing to the possibility that chimerism may be dissociated with tolerance [36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…7 Strikingly, when NOD mice were preconditioned with anti-TCR␤ mAb, significantly impaired engraftment was observed. As for anti-CD4 mAb preconditioning, a higher TBI dose was required compared with TBI-only treated recipients ( Figure 2B).…”
Section: Anti-tcr␤ Mab Pretreatment Of Nod Mice Impairs Engraftmentmentioning
confidence: 99%
“…Surprisingly, the elimination of recipient ␣␤-TCR ϩ T cells significantly impaired engraftment in NOD mice, in contrast with the enhanced engraftment observed after ␣␤-TCR ϩ mAb preconditioning in nonautoimmune mice. 7 Similarly, treatment of the NOD recipients with anti-CD4 mAb abrogated the engraftment-enhancing effect of anti-CD8 mAb treatment alone and actually increased the minimum TBI dose to above that for TBI alone. The combination of anti-CD152 and anti-CD154 mAb similarly abrogated the increased engraftment observed when either reagent was used alone.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations